2018
DOI: 10.1073/pnas.1701392115
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Lagrangian swirls among submesoscale motions

Abstract: The emergence of coherent Lagrangian swirls (CLSs) among submesoscale motions in the ocean is illustrated. This is done by applying recent nonlinear dynamics tools for Lagrangian coherence detection on a surface flow realization produced by a dataassimilative submesoscale-permitting ocean general circulation model simulation of the Gulf of Mexico. Both mesoscale and submesoscale CLSs are extracted. These extractions prove the relevance of coherent Lagrangian eddies detected in satellitealtimetry-based geostrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 40 publications
3
50
0
Order By: Relevance
“…We extract the velocity field from such a model, apply different levels of filtering, and calculate a range of Lagrangian mixing and transport diagnostics. This study can thus Journal of Advances in Modeling Earth Systems 10.1029/2018MS001508 be seen as an update to an extension of prior work by Beron-Vera (2010), Rypina et al (2012), Haza et al (2016), and Beron-Vera, Hadjighasem, et al (2018).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…We extract the velocity field from such a model, apply different levels of filtering, and calculate a range of Lagrangian mixing and transport diagnostics. This study can thus Journal of Advances in Modeling Earth Systems 10.1029/2018MS001508 be seen as an update to an extension of prior work by Beron-Vera (2010), Rypina et al (2012), Haza et al (2016), and Beron-Vera, Hadjighasem, et al (2018).…”
Section: Introductionmentioning
confidence: 75%
“…The authors speculated that this failure could be an artifact of the data assimilation process, related to more general challenges of ocean data assimilation in the submesoscale regime (Sandery & Sakov, 2017). Studying the same eddy, however, Beron-Vera, Hadjighasem, et al (2018) reached a slightly different conclusion: While the geodesic eddy method was too strict to find any Lagrangian coherent structure, the LAVD method was more successful. With a high enough choice of CD, mesoscale eddies were shown to persist, even though their boundaries exhibited increased filamentation relative to the extremely coherent boundaries inferred from satellite altimetry.…”
Section: 1029/2018ms001508mentioning
confidence: 99%
“…Examples of relevant aspects include clustering at the center of the subtropical gyres 18,19 , phenomenon supported on measurements of plastic debris concentration 7 and the analysis of undrogued drifter trajectories 18,19 , or the role of mesoscale eddies as attractors or repellers of inertial particles depending on the polarity of the eddies and the buoyancy of the particles 19,27,28 despite the Lagrangian resilience of their boundaries [48][49][50][51] , which is also backed on observations 52 . The cited phenomena, which act on quite different timescales, all require both O(1) and O(τ ) terms in (12) for their description 18,19,27,28 consistent with the slow manifold M τ in (14), rather than the critical M 0 , controlling the time-asymptotic dynamics of the τ → 0 limit of the Maxey-Riley set (5).…”
Section: Clarification Of the Maxey-riley Setmentioning
confidence: 87%
“…also Gatignol 9 ), yet with a form of the added mass term different than (14), which corresponds to the correction due to Auton, Hunt, and Prud'homme 10 . A Maxey-Riley model with lift force, which has not been so far considered in ocean dynamics despite its relevance in the presence of unbalanced (submesoscale) motions (e.g., Beron-Vera et al 42 ), can be found in Montabone 43 , Chapter 4 (cf. similar forms in Henderson, Gwynllyw, and Barenghi 44 , Sapsis et al 45 ).…”
Section: A the Original Fluid Mechanics Formulationmentioning
confidence: 99%